Análisis fitoquímico y efecto sinérgico protector de las hojas de minthostachys mollis y malva sylvestris sobre la mucosa gástrica de rattus rattus var. albinus - Castillo Saavedra, Ericson Félix (2010)
The peptic ulcer is a lesion that affects an area of the gastrointestinal mucose usually in the stomach or duodenum produced by a disbalance between defensives and protects factors. This report was oriented on determinating phytochemistry of Minthostachys mollis (Kunth) Griseb, Malva sylvestris L., and analyze if these plants in study had synergistic protect effect in the acute injure of gastric mucose induced by ethanol in Rattus rattus var. albinus. Phytochemical screening was realized using Olga Lock technique (test to drop), reporting presence of saponins, tannins, phenolics compounds, flavonoids, steroids and leucoanthocyanins to Minthostachys mollis (Kunth) Griseb; saponins, phenolics compounds, flavonoides and steroids to Malva sylvestris L. Fifty rats were used, divided in five treatment groups: control, reference and problem I, II and III, receiving treatment for five days with physiology saline solution, sucralfate (500 mg/kg) and Minthostachys mollis (Kunth) Griseb (0.4 g/Kg/día), Malva sylvestris L. (0.8 g/Kg/día) y Minthostachys mollis (Kunth) Griseb (0.2 g/Kg/día) + Malva sylvestris L. (0.4 g/Kg/día) respectively; then, 1 mL absolute ethanol was administrated. It was found that Minthostachys mollis (Kunth) Griseb, Malva sylvestris L. and its combination had protect effect against the acute injury of gastric mucose induced by ethanol in Rattus rattus var. albinus, evidenced by low number and diameters of gastric ulcers.